Assessment of functional movement screen and performance parameters of wrestlers using inertial sensors - Khuyagbaatar, B.; Dambadarjaa, B.; Altan-Ochir, Z.; Battumur, G.; Batbaatar, E.; Kim, Y. H. (Frontiers in Sports and Active Living, 2025)
A functional movement screen (FMS) is an assessment system that identifies athletes' movement profiles and injury risks. This is also used to determine sport-specific performance and training effectiveness. However, none of the studies have employed the IMU measurement system to assess FMS and performance parameters in wrestling. In this study, we aimed to assess FMS and kinematic parameters in wrestlers using IMU sensors to explore the relationship between FMS scores, range of motion (ROM), and performance parameters. Ten healthy controls and ten wrestlers completed the seven tasks of the FMS and performed wrestling techniques. The screening results were assessed, revealing significant differences in shoulder mobility (Control: 2.7 ± 0.6, Wrestlers: 1.9 ± 0.8) (p = 0.034, Cohen's d = 1.02) and active leg raise tests (Control: 2.3 ± 0.4, Wrestlers: 2.9 ± 0.3) (p = 0.004, Cohen's d = 1.47) between the two groups. Additionally, center of mass (CoM) velocity increased by 18%, while CoM position lowered by approximately 5%-8% during wrestling techniques in the higher FMS group. This study demonstrated the convergent validity of FMS scores with joint mobility and performance parameters in wrestling techniques. We assessed athletes` ability to correctly perform movements using the FMS scoring system and analyzed kinematic parameters, including the displacement and velocity of the CoM, through wearable inertial sensors. Our findings indicate that higher FMS scores are associated with greater CoM velocity and the ability to maintain a low CoM position during wrestling.